A prospective comparative study and analysis of predictors of SUNA and SUNCT. (17th September 2019) - Lambru, Giorgio; Rantell, Khadija; Levy, Andrew; Matharu, Manjit S.
Abstract : Objective: Despite the similar phenotypes, comparison between short-lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing (SUNCT) and short-lasting unilateral neuralgiform headache attacks with autonomic features (SUNA) has hitherto not been possible due to the dearth of studies validating the phenotype of SUNA. Therefore, these 2 syndromes have been kept separate in the International Classification of Headache Disorders. The aim of this study is to characterize and compare the clinical phenotypes of large clinic-based cohorts of patients with SUNA and SUNCT. Methods: The clinical phenotype of consecutive patients with SUNA identified from a single specialist headache center in the United Kingdom between 2007 and 2012 was studied and compared to that of patients with SUNCT. Results: Sixty-three patients with SUNA (18 male, 28.6%) and 70 patients with SUNCT (32 male, 35.7%) were included. The demographic and clinical characteristics of patients with SUNA were similar to those of patients with SUNCT. Ptosis and rhinorrhea were predictors of SUNCT. The corresponding odds ratios (ORs) (95% confidence interval) were 3.79 (1.64–8.77, p = 0.002) and 2.46 (1.09–5.59, p = 0.031), respectively. The presence of spontaneous only attacks was a predictor for SUNA (OR 2.58 [1.10–6.05], p = 0.029). Conclusion: No major clinical differences have emerged between SUNCT and SUNA, bar the fact that SUNCT is characterized by more prominent cranial autonomic features and triggerability. We propose that the 2 disorders be placed together in a single diagnostic category for which new diagnostic criteria are proposed.